Cardio-Oncology: Learning From the Old, Applying to the New - Abe, Jun-ichi; Yusuf, Syed Wamique; Deswal, Anita; Herrmann, Joerg (Frontiers in Cardiovascular Medicine, 2020)
The recent surge in cancer drug approval has provided us in cardio-oncology with a new and unique era, which modern medicine has not experienced before: the diminishing availability of “conventional” evidence-based medicine. The drastic and quick changes in oncology has made it difficult, and at times even impossible, to establish a meaningful evidence-based cardio-oncology practice by simply following the oncologists’ practice. For the modern cardio-oncologist, it seems that a more proactive approach and methodology is needed. We believe that only through such an approach (learn from the old, and apply to the new) the cardio-oncologist will obtain meaningful evidence to perform their every-day practice in this new era.